2014
DOI: 10.1242/jeb.098673
|View full text |Cite
|
Sign up to set email alerts
|

Colouration principles of nymphaline butterflies - thin films, melanin, ommochromes and wing scale stacking

Abstract: The coloration of the common butterflies Aglais urticae (small tortoiseshell), Aglais io (peacock) and Vanessa atalanta (red admiral), belonging to the butterfly subfamily Nymphalinae, is due to the species-specific patterning of differently coloured scales on their wings. We investigated the scales' structural and pigmentary properties by applying scanning electron microscopy, (micro)spectrophotometry and imaging scatterometry. The anatomy of the wing scales appears to be basically identical, with an approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 45 publications
6
147
0
Order By: Relevance
“…The measured absorbance spectra of our various scale types (Fig. 3D) do not match the melanin absorbance spectrum exactly (30,32,33), indicating that brown scales in B. anynana either do not contain melanin or, more likely, contain additional pigments besides melanin. Because the type and amount of pigments that exist in the lower lamina of scales are not known, we cannot accurately estimate the change of refractive index value caused by pigmentation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The measured absorbance spectra of our various scale types (Fig. 3D) do not match the melanin absorbance spectrum exactly (30,32,33), indicating that brown scales in B. anynana either do not contain melanin or, more likely, contain additional pigments besides melanin. Because the type and amount of pigments that exist in the lower lamina of scales are not known, we cannot accurately estimate the change of refractive index value caused by pigmentation.…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies on butterflies showed that structural color can be produced by interference with light reflected from the overlapping lamella that build the longitudinal ridges, from microribs protruding from the sides of the longitudinal ridges, or from the lower lamina, which can vary in thickness and patterning (Fig. 1J) (29,30). However, it is not clear how the violet/blue color is produced in members of the two Bicyclus clades that separately evolved this color, whether B. anynana can be made to evolve the same violet/blue color via artificial selection, and whether it will generate the color in the same way as the other species.…”
mentioning
confidence: 99%
“…In reflected light, both pigmentary and structural colours are visible, but only pigmentary colours are visible under transmission illumination (Land et al, 2007;Stavenga et al, 2014;Vukusic et al, 1999).…”
Section: Reflected/transmitted Light Microscopymentioning
confidence: 99%
“…Each different morphology changes the way light interacts with the structure, as do local defects and disorder. Insect nanomorphologies range from ordered structures starting from thin films [309][310][311] and multilayer structures [277,282,304,312,313] to 3D photonic crystals to quasi-ordered and fully disordered structures, [314][315][316][317][318][319][320] each with different optical properties.…”
Section: Structural Colorationmentioning
confidence: 99%